Protection and compliance of Human Rights of Residents Affected by the Semeru Eruption - Achmad Hariri; Samsul Arifin Ari; Satria Unggul Wicaksana Prakasa; Asis Asis (Universitas Muhammadiyah Malang, 2022)
The eruption of Mount Semeru had a major impact on the surrounding communities affected. Not only about health, but these natural disasters also affect other aspects such as the economy, education, clean water facilities, and residential areas. The fulfilment of these rights is actually regulated in the International Covenant on economic, social, and cultural matters. Any country subject to such rules is insufficient to grant the right to access Education. Still, the state is obliged to provide Educational facilities, and the existing social and Educational facilities will necessarily suffer damage due to natural disasters. From these problems, this study aims to understand and elaborate on legal responsibility, protection and fulfilment of human rights for residents affected by the Semeru eruption. The method used in this research is Socio-Legal based legal research with an approach of Participatory Action Research (PAR).